Comparative Effects of Metformin and Glibenclamide on Aortic Reactivity to Vasodilator and Vasoconstrictor Agents in STZ-Induced Diabetic Rats: Comparative effect of metformin and glibenclamide in diabetic rats - Mohebbati, Reza; Hayatdavoudi, Parichehr; Abbasnezhad, Abbasali (Iranian Journal of Pharmaceutical Sciences, 2018)
Diabetes is an important risk factor for cardiovascular events. Endothelial dysfunction is the main cause of disability and death in diabetic patients. The present study investigates the effects of metformin and glibenclamide on vasoconstrictive and vasodilative responses in the diabetic rat aorta. Rats were divided into four experimental groups (control, STZ-diabetic, metformin and glibenclamide treated diabetic rats). The treated rats received metformin (300 mg/kg) or glibenclamide (5 mg/kg) daily by gavage for 6 weeks.Thoracic aortic rings were mounted in an organ bath system, then contractile and dilatation responses induced by acetylcholine (ACh), phenylephrine (PE), potassium chloride (KCl), and sodium nitroprusside (SNP) were evaluated in different situations.Blood glucose level in glibenclamide group in days 24 and 45 were significantly lower than diabetic group. Metformin and glibenclamide significantly reduced the contractile responses to higher concentrations of PE (10-6 - 10-5 M) compared to diabetic group. Metformin and glibenclamide significantly reduced the contractile responses to concentrations of KCl (50 and 60 mM) compared to diabetic group. The relaxation responses to Ach 10-8 M, was increased in metformin and glibenclamide groups compared to the diabetic group. The relaxation responses to Ach 10-7 - 10-5 M were significantly higher in both treated groups compared to diabetic group. The chronic administration of metformin or glibenclamide has a significant hypoglycemic effect and improves aortic reactivity to vasoconstrictor and vasodilator agents in STZ-induced diabetic rats. No significant difference was found regarding the effects of metformin and glibenclamide on vasoconstrictive and vasodilative responses in aorta.